2016
DOI: 10.1111/lit.12086
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of reading in the age of digitisation: an integrative framework for reading research

Abstract: In the course of digitisation, the range of substrates for textual reading is being expanded to include a number of screen-based technologies and reading devices, such as e-readers (e.g. Kindle) and tablets (e.g. iPad). These technologies have distinctly different affordances than paper has. Given that textual reading is at the same time likely to remain important as a cultural practice, and is undergoing massive change as digital screens are supplementing paper -with the potential to replace it as the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 44 publications
(37 reference statements)
1
87
1
15
Order By: Relevance
“…In relation to the approaches towards print and digital literacies, Sefton‐Green et al () write that a mono‐level approach “is somewhat of a paradox in an era reliant on digital devices both in the home and in the knowledge society, where means and forms of communication have diversified” (p. 12). Mangen and van der Weel () call for more interdisciplinary approaches to children's reading on screen and based on our findings, we extend this call to children's writing on screen. Also, participatory literacies could usefully inform future studies of children's writing on screen.…”
Section: Resultsmentioning
confidence: 54%
“…In relation to the approaches towards print and digital literacies, Sefton‐Green et al () write that a mono‐level approach “is somewhat of a paradox in an era reliant on digital devices both in the home and in the knowledge society, where means and forms of communication have diversified” (p. 12). Mangen and van der Weel () call for more interdisciplinary approaches to children's reading on screen and based on our findings, we extend this call to children's writing on screen. Also, participatory literacies could usefully inform future studies of children's writing on screen.…”
Section: Resultsmentioning
confidence: 54%
“…Finally, heeding Mangen and van der Weel's () call for integrating the social and embodied perspectives on reading through also combining research methods that have traditionally been practised in mutual isolation, we see the present exploratory study as a first step towards research designs wherein participants' reading experience and performance will be observed and measured in controlled or semi‐controlled experimental environments, and across different bodily and social conditions. Informed by qualitative studies like the one presented here, such designs could provide generalizable evidence for improved practice in the fields of literacy, education, library studies and reading promotion.…”
Section: Resultsmentioning
confidence: 99%
“…Con el fin de hacer una comparativa en ambos países en los mismos años, estos períodos se irán ajustando. Este criterio de clasificación cronológica responde a que, tras la aparición de la web, las perspectivas metodológicas de estudio de la lectura se han modificado, introduciendo un conjunto de variables ergonómicas, perceptivas, cognoscitivas, emocionales, fenomenológicas, y socioculturales, ofreciendo así una dimensión multidisciplinar de la investigación (Mangen; Van der Weel, 2016). De esta manera, el factor sociocultural adquiere gran importancia en este sentido, motivo por el cual es objeto de este estudio.…”
Section: Metodologíaunclassified